African historical religions and Africana spirituality in the Caribbean literature: an analysis of Afro-Caribbean philosophical archetypes in contemporary Caribbean literature using Ifá philosophy as a signifying system - De La Cruz, Garcia Katia (School of Languages and Literatures, 2019)
This research analyses the presence of Afro-Caribbean philosophical archetypes in Caribbean literature as fundamental elements in the identity formation and racial dynamics of African descendants in the Caribbean. The main focus is on the spiritual component of African historical religions and Africana spirituality. The spiritual component, considering its level of transcendence in the human being, is essential in the formation of the identity since it allows the creation of moral archetypes that can be recognized in literary creations. The research uses Ifá philosophy, Yoruba mythology, and Africana religions, as signifying systems. The research considers the religious foundations of the Ewe-Fon, Kongo and especially, Yoruba traditions, with a focus on the Yoruba Oracle as Literary Corpus as well as the basis for the analysis of the following novels: Of Love and other Demons by Gabriel García Márquez, Changó, the biggest badass by Manuel Zapata Olivella, Ecué Yamba Ó by Alejo Carpentier, The red of his shadow by Mayra Montero and Gabriela, clove and cinnamon by Jorge Amado. This project establishes that the moral philosophy, implicit in the divinatory system of the Yoruba people, known as Ifá, can be traced through the literary structures of Caribbean literature and can be used as a reference for transnational identity in the Caribbean.